Design, Making and the Digitisation Trap - Andrea Cattabriga; Luca Barbieri (DIID, 2021)
The article aims to investigate the evolutionary dynamics and critical issues emerging around makerspace communities, collaborative design and prototyping spaces whose practices have radically impacted the world of education, enterprise and social innovation. Through an exploratory approach, experts from the maker movement and design students have been involved to understand the health of the model underlying makerspaces. The perspective of the research is to graft the debate on the forms of these practices into the dichotomy between physical and digital, socialization practices of design and the ability of these bottom-up models to work on complex solutions. A list of recurring conditions occurring at the time of the creation of these communities has been elaborated. The discussion then covers risks and limitations of the physical dimension of makerspaces in relation with digitization of operations and relations at every level, calling for a necessary re-thinking of co-design practices.